Bionic UAV architecture for fast swarm fusion - Ziming ZENG; Chao DONG; Xiaojun ZHU; Ziye JIA (Dianxin kexue, 2022)
UAV swarm operation is an important part of the future battlefield.UAVs in the cluster cooperate to complement each other and coordinate tasks to improve the overall performance of the system.In animal groups such as ants, wolves, pigeons, fish, etc., their individuals behave similarly to a single drone, while ant colonies, wolves, and pigeon colonies can rely on the rules between individuals to achieve more complex behaviors through group coordination and organization.Different creatures exhibit different abilities and can undertake different tasks on the battlefield.Considering the topology and communication mechanism between creatures, a fusion architecture of bionic drone swarms was proposed which aims to enable different types of bionic UAV swarms to be freely integrated and improve the coordination level of the whole UAV swarm architecture.